CLINICAL CHARACTERISTICS OF PREMATURE INFANTS WITH RESPIRATORY DISTRESS SYNDROME - Mukhamedova Shakhnoza Tolibovna; Rasulova Ogiloy Nematjon qizi (Web of Journals Publishing, 2025)
Respiratory distress syndrome (RDS) is a serious pathological condition that occurs most often in premature infants, resulting from a lack of pulmonary surfactant. This article discusses the clinical characteristics of premature infants with RDS, the severity of the disease, diagnostic methods, and treatment tactics. It also analyzes the effectiveness of modern preventive measures and treatment methods.
Keywords: Respiratory distress syndrome, premature babies, surfactant, mechanical ventilation, perinatal pathology.